Out of Africa - Mirage Production (Mirage Production, 1985)
Out of Africa is the fascinating true story of Karen Blixen, a strong willed woman who, with her philandering husband (Klaus Maria Brandaver), runs a caffee plantation in Kenya, to her astonishment she soon discovers herself falling in love with the land, its people and the mysterious white hunter, Robert Redfort